Pesticide Effects on Nontarget Organisms - Frederick M. Fishel (EDIS)
This guide addresses the effects of various types of pesticides on nontarget organisms, including natural enemies and beneficial organisms such as honey bees, wildlife, fish, and nontarget plants. This document is PI-85, one of a series of the Pesticide Information Office, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: November 2005.